2001
DOI: 10.1016/s0002-9440(10)63068-4
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin K Is a Critical Protease in Synovial Fibroblast-Mediated Collagen Degradation

Abstract: Synovial fibroblasts (SFs) play a critical role in the pathogenesis of rheumatoid arthritis (RA) and are directly involved in joint destruction. Both SF-resident matrix metalloproteases and cathepsins have been implicated in cartilage degradation although their identities and individual contributions remain unclear. The aims of this study were to investigate the expression of cathepsin K in SFs, the correlation between cathepsin K expression and disease severity, and the contribution of cathepsin K to fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
135
0
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 167 publications
(145 citation statements)
references
References 38 publications
(48 reference statements)
4
135
0
6
Order By: Relevance
“…An up-regulation of cathepsin K in synovial fibroblast-like cells has also been reported in both rheumatoid and osteoarthritis (Hou et al, 2001(Hou et al, , 2002Hummel et al, 1998). In rheumatoid arthritis cathepsin K-positive cells were observed in areas of high proliferation within the synovium and at sites of cartilage and bone degradation (Hou et al, 2001).…”
Section: Synovium: Inflammation Hyperplasia Pannus Formation and Prmentioning
confidence: 91%
See 4 more Smart Citations
“…An up-regulation of cathepsin K in synovial fibroblast-like cells has also been reported in both rheumatoid and osteoarthritis (Hou et al, 2001(Hou et al, , 2002Hummel et al, 1998). In rheumatoid arthritis cathepsin K-positive cells were observed in areas of high proliferation within the synovium and at sites of cartilage and bone degradation (Hou et al, 2001).…”
Section: Synovium: Inflammation Hyperplasia Pannus Formation and Prmentioning
confidence: 91%
“…An up-regulation of cathepsin K in synovial fibroblast-like cells has also been reported in both rheumatoid and osteoarthritis (Hou et al, 2001(Hou et al, , 2002Hummel et al, 1998). In rheumatoid arthritis cathepsin K-positive cells were observed in areas of high proliferation within the synovium and at sites of cartilage and bone degradation (Hou et al, 2001). Ex vivo studies demonstrated engulfment and internalization of type II collagen by fibroblast-like synoviocytes at sites of cartilage erosion and its accumulation within lysosomes in the presence of a cathepsin K inhibitor (Hou et al, 2001).…”
Section: Synovium: Inflammation Hyperplasia Pannus Formation and Prmentioning
confidence: 91%
See 3 more Smart Citations